Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Terhadap Hasil Belajar Teknik Dasar Passing Bola Basket - Garry William Dony; Bernisa Bernisa; Yossita Wisman (FKIP Universitas Palangka Raya, 2024)
This research aimed fo know the effect of cooperative learning model, its type was student teams achievement division (STAD) to learning output of basic technique passing of basket ball (chest pass and over head pass). This research by using the pre-test post-test control group design. This research was done to seventh grade students in SMP Negeri 9 Palangka Raya academic year 2023/2023 with sampel which were 52 students. They were distributen into two classes namely VIIB and VIIF classes it classes namely VIIB and VIIF classes. It used simple random sampling data of learning outcome consists of 1.) cognitive aspect using multiple choice test, 2.) affective aspect, using students attitude observation, 3.) psychomotoric aspect, using basket ball passing observation. Analyzing data consists of. 1.) prerequisite test, using normality test applying kolmogorov-smirnov and homogeneity test applying Levene’s test of equality of error variance, and 2.) hypothesis test, using t-test on significant standard 0.05. According prerequisite test it was got the result that data have normal distribution and homogent t-test showed that tcount = 4.334 while ttable =1675, and it has significant value using t-test which was p<0.00. Supporting the result of analyzing data and discussion, the candusion of this research is implementation of cooperative learning model STAD had significant effect on learning output of basket ball passing of 7 th-grade students in SMP Negeri 7 Palangka Raya academic year 2023/2023. Heance,it hoped that penjasorkes teachers can apply cooperative learning model STAD type, because it was seen that it has significant effect on students learning outcome.